The Development of Teaching Materials to Write Description Text Based on the Local Wisdom of Pulau Rakyat in VII Grade of SMP Swasta Swadaya Pulau Rakyat - Efrina Efrina; Mutsyuhito Solin; Amrin Saragih (BIRCU, 2020)
This study aims to determine the developing. The form of teaching materials used by teachers is still based on textbooks provided in schools, namely books from the Ministry of Education and Culture. Another factor that influences the lack of developed teaching materials is creativity to plan, prepare and make teaching materials. This is also confirmed in Prastowo's book (2015: 14), that the general paradigm and perception inherent among educators is that making teaching materials is a difficult and stressful job. So, the teacher is reluctant to think about finding out how to develop teaching materials. This research was conducted at the Pulau Rakyat Private Junior High School, Asahan Regency, North Sumatra to grade VII students. The implementation of this research was carried out in the even semester of 2019. The results of the effectiveness of teaching materials for writing descriptive text based on local wisdom of Pulau Rakyat on a limited trial were 32 students of class VII of the Private Island Private Junior High School, namely the results of the pretest trial obtained an average score of 69.5 with sufficient category. Meanwhile, the student learning outcomes after using the teaching materials to write descriptive texts based on the local wisdom of the Island of the People / postest with an average score of 77.3 in a good category.